2.79 μm laser performance of a 968 nm LD side-pumped Er:LuYSGG mixed crystal. Issue 26 (10th June 2022) - Dong, Kunpeng; Sun, Dunlu; Zhang, Huili; Luo, Jianqiao; Zhao, Xuyao; Quan, Cong; Hu, Lunzhen; Han, Zhiyuan; Qiao, Yang; Chen, Yuwei; Cheng, Maojie
Abstract : We demonstrate the laser performance of a 968 nm LD side-pumped Er:LuYSGG crystal rod by optimizing the cavity length and output coupler transmission. Abstract : We demonstrate the laser performance of a 968 nm LD side-pumped Er:LuYSGG crystal rod by optimizing the cavity length and output coupler transmission. The maximum output power of 14.84 W is obtained at 150 A, 150 Hz, and 200 μs, corresponding to a slope efficiency of 17.2%. Under the high frequency of 500 Hz and short pulse width of 60 μs, an average output power of 7.27 W is achieved, corresponding to a slope efficiency of 7.1%. Additionally, beam quality factors M x 2 /M y 2 of 7.04/7.12 at 150 Hz and an average output power of 11.33 W are also determined. These results can provide valuable references for promoting the development of 2.7–3 μm lasers.